Fuzzy Logic Modeling Metode Sugeno Pada Penentuan Tipe Diabetes Melitus Menggunakan MATLAB - Rico Adrial (Teknik Informatika, 2018)
Mellitus Diabetic already known since thousands of years before, where characterized by urine in the much amount. This leds serious investigation to heal patients. Fuzzy Logic is one of support system decision method that suitable for implementation at an election of diabetic type. It is because fuzzy logic is a system than can calculate and decided well. There are various methods in fuzzy logic such as Mamdani, Tuskamoto and Sugeno. In this article Sugeno Method is used because its calculation suitable in this case. The research is done by using MATLAB. It has been built an application in the health sector to choose type of mellitus diabetic using fuzzy logic Sugeno. The decision making of diabetic type needs input and output variables. The input variable consists of ages, levels of insulin and weights beside output variable consist of diabetic type using MATLAB. Variables produce 27 rules that used to determine of diabetic type. The support system decision for diabetic type with Sugeno method is used. A case obtained the very small difference value between using manual calculation and MATLAB.